Social Media and Policy Making in Pakistan - Fiaz Hussain (Pakistan Administrative Review, 2018)
The study highlights the role of social media and policy making in Pakistan. For this purpose, case study methodology has been employed. The study examines trend analysis of different public problems being discussed on social media (Twitter). Four cases have been selected purposefully. The trend analysis of selected public problems show that twitter users expressing their views. Transgender case of Alisha was identified highlighted by social media. Consequently, the KPK government took the notice of the case and allocated Rs. 200 million for the transgender community. The issue of Panama leak has been debated inside and outside of the Parliament of Pakistan. Social media users have also participated in the discussion and have floated their suggestion to resolve the issue. The problem of malnutrition in Baluchistan was also identified and highlighted on social media. Subsequently, the government of Baluchistan took the notice of the problem and introduced the ‘Scaling up Nutrition’ for malnutrition women and children in Baluchistan. Honor killing cases have been the hot topics among social media users. The case of Zeenat Bibi was also debated on social media. Parliament of Pakistan has taken up the issue and passed a law related to honor killing. Social media is vibrant, dynamic media.